Molecular rheotaxis directs DNA migration and concentration against a pressure-driven flow - Sarah M. Friedrich (Nature Portfolio, 2017)
Implementing a nucleic acid preconcentration method can improve the sensitivity of microfluidic analysis systems. Here Friedrich et al. concentrate DNA by many orders of magnitude using pressure-driven flow, which could lead to a simple and practical microanalysis platform.